The validity and reliability of a novel indoor player tracking system for use within wheelchair court sports - Rhodes, J.; Mason, B.; Perrat, B.; Smith, M.; Goosey-Tolfrey, V. L. (Journal of Sports Sciences, 2014)
The aim of the current study was to investigate the validity and reliability of a radio frequency-based system for accurately tracking athlete movement within wheelchair court sports. Four wheelchair-specific tests were devised to assess the system during (i) static measurements; (ii) incremental fixed speeds; (iii) peak speeds; and (iv) multidirectional movements. During each test, three sampling frequencies (4, 8 and 16 Hz) were compared to a criterion method for distance, mean and peak speeds. Absolute static error remained between 0.19 and 0.32 m across the session. Distance values (test (ii)) showed greatest relative error in 4 Hz tags (1.3%), with significantly lower errors seen in higher frequency tags (<1.0%). Relative peak speed errors of <2.0% (test (iii)) were revealed across all sampling frequencies in relation to the criterion (4.00 ± 0.09 m/s). Results showed 8 and 16 Hz sampling frequencies displayed the closest-to-criterion values, whilst intra-tag reliability never exceeded 2.0% coefficient of variation (% CV) during peak speed detection. Minimal relative distance errors (<0.2%) were also seen across sampling frequencies (test (iv)). To conclude, the indoor tracking system is deemed an acceptable tool for tracking wheelchair court match play using a tag frequency of 8 or 16 Hz.